1983
DOI: 10.1590/s0074-02761983000200011
|View full text |Cite
|
Sign up to set email alerts
|

Nota sobre Lutzomyia (Trichopygomyia) Dasypodogeton (Castro, 1939), com a redescrição do macho e da fêmea (Diptera: Psychodidae, Phlebotominae)

Abstract: Os autores, após transcreverem a descrição original da Lutzomyia (Trichopygomyia) dasypodogeton (Castro, 1939), inicialmente publicada de maneira muito resumida em jornal não científico, redescrevem, de acordo com as normas atualmente adotadas, ambos os sexos dessa espécie, inclusive com desenhos dos elementos taxonomicamente importantes. É, também, dada uma chave para a identificação das espécies do subgênero trichopygomyia Barreto, 1952.
After a transcription of the original description of Lutzomyia (Tric…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A recent study shows that this particular species is found in abundance in the Northern region of MT (17) . This may be due to the presence of armadillos in the region, which are considered a reservoir for Leishmania (18) . We observed the presence of armadillo burrows in the APPs during the installation of traps, which could have contributed to the high frequency of this species in these areas.…”
Section: Gender (%)mentioning
confidence: 99%
“…A recent study shows that this particular species is found in abundance in the Northern region of MT (17) . This may be due to the presence of armadillos in the region, which are considered a reservoir for Leishmania (18) . We observed the presence of armadillo burrows in the APPs during the installation of traps, which could have contributed to the high frequency of this species in these areas.…”
Section: Gender (%)mentioning
confidence: 99%